Islamophobia dan Tindakan terhadap Minoritas Muslim oleh Pemerintah dan Kelompok 969 di Myanmar Tahun 2012-2016 - Hapsari, Renitha Dwi (Global and Policy Journal of International Relations, 2016)
ABSTRACTIslamophobia has become a global phenomenon since 9/11. It is not only happened in the West but spread around the world following the War on Terror policy. This article explains the influences of Islamophobia upon the rise of Buddhist Nationalism in Myanmar with its insecurity towards Moslem minorities within the country. As a rational response against Islamophobia, a number Buddhist extremists, such as 969, execute violent attacks towards Moslem minorities especially Moslem Rohingya. Patron-client relationship between the Government and Buddhist community make the violence even worse. In the end, Islamophobia and the rise of Buddhist Nationalism in Myanmar cause a prejudice, violence, discrimination, and exclusion towards all Muslim Minorities within the country.Keywords: islamophobia, the rise of Buddhist nationalism, patron-client, prejudice, exclusion, discrimination, violence, Myanmar, moslem minoritiesDOI : https://doi.org/10.33005/jgp.v4i02.1911